The Influence of Leadership, Organizational Commitment, and Work Culture on Employee Competence and Performance with Moderation of Employee Development Policies at the Education Office of North Sumatra Province - Maludin Panjaitan; Azhar Affandi; Heru Setiawan; Sidik Priadana; Umi Narimawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The success of education and teaching at private universities in North Sumatra Province will depend heavily on the quality of lecturers who are able to produce high lecturer performance. which in the end will be able to improve the performance of the private university. This study aims to identify, analyze and examine Visionary Leadership, Organizational Culture, and Lecturer Competence on Affective Commitment and Job Satisfaction and Their Implications for Lecturer Performance at Private Universities in North Sumatra. This study used a quantitative method with a descriptive analysis and verification analysis approach. In this study, the sample was the lecturers who received the fixed income with a sample of 212 lecturers. The method of analysis in this study uses path analysis (path analysis). The results of the study concluded that: 1). There is a significant influence from Visionary Leadership, Organizational Culture, and Lecturer Competence on Affective Commitment, with a magnitude of influence of 73.18 percent 2). There is a significant influence from Visionary Leadership, Organizational Culture, and Lecturer Competence on Job Satisfaction with an influence of 75.11 percent, and 3) there is a significant influence. of affective commitment and job satisfaction on lecturer performance with an influence size of 85.57 percent. 11 percent, and 3) there is a significant effect. of affective commitment and job satisfaction on lecturer performance with an influence size of 85.57 percent. 11 percent, and 3) there is a significant effect. of affective commitment and job satisfaction on lecturer performance with an influence size of 85.57 percent.